Communication Management of the Waste Management Movement in Cokrodiningratan Village, Yogyakarta City Year 2023 - Efendi, Ghaidza Annisa Putri; Ridho, Subkhi; Irfanudin, Fahmi (GoAcademica Research & Publishing, 2025)
Garbage is a major problem in Yogyakarta City. Cokrodiningratan Village has a waste management program that involves the community. Effective communication management is the key to the success of the program. This study aims to analyze communication management in the waste management movement in Cokrodiningratan Village, Yogyakarta City, in 2023. Using a qualitative approach, this study explores strategies, policies, and implementation of communication used by related parties in managing waste at the village level. Through in-depth interviews with stakeholders as well as direct observation, this study explores the role of communication in raising public awareness and participation in the waste management movement. There are several communication channels used: such as Regular meetings: socialization, and education to the community about waste management. Social media: dissemination of information and announcements related to waste management programs. Banners and posters: visual information media to increase public awareness. Effective communication management is the key to the success of the waste management movement in Cokrodiningratan Village. Efforts are needed to improve the quality of communication and build active community participation in protecting the environment. The results of this study are expected to provide deep insight into the importance of effective communication management in supporting the success of waste management programs at the local level. This research shows that communication management in the waste management movement in Cokrodiningratan Village is quite good.